Positive Politeness Strategies Used in Oprah’s 2020 Vision Tour Visionaries: The Rock Interview - I Wayan Nanditha Kusanaghi; I Nengah Sudipa; I Made Rajeg (CV. Ulil Albab Corp, 2023)
This article is entitled Positive Politeness Strategies Used In Oprah’s 2020 Vision Tour Visionaries: The Rock Interview. It focuses on the positive politeness strategies in a talk show entitled Oprah’s 2020 Vision Tour Visionaries. The aims of this study are to identify the types of positive politeness strategies employed by Oprah Winfrey and Dwayne Johnson and explain the reasons and factors that influenced the participants in Oprah’s 2020 Vision Tour Visionaries. The data was taken from the utterances between Oprah Winfrey and Dwayne Johnson in the talk show. The data were collected through documentation method by note-taking technique. This article used Brown and Levinson theory (1987) of positive politeness strategies as the main theory as well as to identify the types of positive politeness strategies and to analyze the reasons and factors influencing the use of positive politeness strategies in Oprah’s 2020 Vision Tour Visionaries: The Rock Interview. The results of this study show that twelve strategies of positive politeness strategies proposed by Brown and Levinson (1987) are found in this article. There were two factors that influenced the choice those positive politeness strategies, namely the payoff: a priori consideration, and The Circumstance: Sociological variable.